Safety and communication glasses / Muhammad Farouq Aiman Mohd Nazari and Muhammad Redza Rosman - Mohd Nazari, Muhammad Farouq Aiman; Rosman, Muhammad Redza (2023)
This study presents the outcomes of an innovation project that focuses on the implementation of safety and communication glasses in enhancing safety and communication aspects in construction industry. The goal of this project is to explore the effectiveness and advantages of having good eye protection besides an effective communication on site. The study begins with an introduction to the significance of effective communication and the limitations of existing approaches. It then provides an overview of the safety and communication glasses, including their principles, components, and advantages. The selected methodology for this study involves 3D modelling simulations.